Dropwise condensation heat transfer on nanostructured superhydrophobic surfaces with different inclinations and surface subcoolings. (December 2021) - Wang, Xin; Xu, Wanting; Chen, Zhenqian; Xu, Bo
Highlights: Wetting transition induced by subcooling and droplet return can flood the condensing surface. The removal mechanism of jumping and sliding droplets at various conditions is analyzed. Self-jumping dynamics of droplet at the various initial states is simulated by LBM. HTC is enhanced by 21.1, 49.2 and 72.4% at α  = 30°, 60° and 90° compared to α  = 0°. If the energy conversion efficiency is below 2.1%, coalesced droplets are stuck to the surface. Abstract: Due to the excellent heat transfer efficiency, dynamic behaviors of coalescence-induced droplet jumping on superhydrophobic surfaces have been extensively investigated to facilitate the technological applications in power generation, refrigeration, and water harvesting. Despite numerous experiments and simulations of vapor condensation, the droplet dynamics and heat transfer performance affected by the combination of initial wetting state and inclination during pure vapor condensation are still poorly understood. Combining visual experiments and lattice Boltzmann simulations, the droplet dynamics, size distribution and heat transfer on the nanostructured surface at various condensing conditions are analyzed. As the subcooling increases from 0.5 to 3.5 K, the jumping frequency of droplets at α  = 90° decreases significantly from 173 to 36 cm −2  s −1 and the average droplet diameter is increased by ∼300%. Meanwhile, the jumping diameter ranges from 20 to 280 μm, with a ∼60% reduction in maximum jumping height. The critical sliding diameters at α  = 30° are 1.5, 1.4 and 1.5 times higher than those at a 90° inclination as the subcoolings are 5.0 K, 6.5 K and 8.0 K, respectively. Heat transfer coefficient is enhanced by 21.1% at α  = 30°, 49.2% at α  = 60°, and 72.4% at α  = 90°. In addition, the LB results demonstrate that if the energy conversion efficiency is below 2.1%, condensate droplets are stuck to the substrate rather than jumping away spontaneously.